2020
DOI: 10.3390/su12198219
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Heritage Management: Exploring Dimensions of Pull and Push Factors

Abstract: While determining sustainable heritage development, it is important to consider how heritage satisfies human needs. The purpose of this study is to explore the pull and push factors in heritage tourism. This study generated 38 initial items of pull factor and 18 initial items of push factor toward heritage tourism to assess the significance of items influencing people’s decision to visit heritage sites. The study obtained 332 valid questionnaires to implement exploratory factor analysis to capture the pull and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Both heritage types (i.e., commercial and recreational) were found significant, meaning that these types of heritages were attractive to people. Considering the supporting products, the increased number of attractions and public toilets in a neighborhood significantly increases the heritage attractiveness; this result was expected because a combination of heritages and services contributes to attractiveness in historical places [5,6]. It is also possible that supporting services and facilities were built because of the existence of cultural heritage in these areas.…”
Section: The Results Of Global Model (Ols)mentioning
confidence: 99%
See 1 more Smart Citation
“…Both heritage types (i.e., commercial and recreational) were found significant, meaning that these types of heritages were attractive to people. Considering the supporting products, the increased number of attractions and public toilets in a neighborhood significantly increases the heritage attractiveness; this result was expected because a combination of heritages and services contributes to attractiveness in historical places [5,6]. It is also possible that supporting services and facilities were built because of the existence of cultural heritage in these areas.…”
Section: The Results Of Global Model (Ols)mentioning
confidence: 99%
“…The combination of historical places and services creates an attractive historic area. Thus, in addition to the location of heritage places, the supporting services and facilities (i.e., public transport stops, eating/drinking facilities) play an important role in their attractiveness [5,6]. For instance, Vong and Ung's (2012) study found that history and culture, facilities and services at heritage sites, heritage interpretation, and heritage attractiveness are distinctive factors for heritage visitors in Macau.…”
Section: Introductionmentioning
confidence: 99%
“…Not all the Sustainable Development Goals (SDGs) are satisfied by any alternative under evaluation. Specifically, the nursing home is more focused on factors related to wellbeing and the sustainable use of natural resources (No 3,6,7,9), the university research center promotes, moreover, the gender equity and good quality of education (No 4,5,7,8,9,15), the food district considers responsible production and consumption by supporting the generation of sustainable cities and communities (No 2,7,8,9,11,12), and the cultural center is the only one concerned with the relationship with the institutions (No 4,10,11,16).…”
Section: Performance Matrixmentioning
confidence: 99%
“…The intervention may also be further subject to limitations by the building regulations in force at the municipal level or by restrictions imposed by specific protection bodies. For this reason, it can be seen that it is not possible to identify a univocal way of operating that can be applied every time we find ourselves having to intervene on an abandoned cultural building [15,16]. Every single intervention needs an approach aimed at providing an optimal solution case by case, regardless of a careful analysis of the building, the surrounding context, and the actors involved in participating in the decision-making process.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain an effective advantage, ICT must be presented in universal and adjustable models, address physical and emotional/experiential dimensions, and consider the different needs and values of the different stakeholders, especially those of the tourist/client [12]. Tourists' and other consumers' decision-making has been studied from different perspectives: from the motivation to consume (the push factor) [13,14] to the attractiveness of the destination or product (the pull factor) [15,16], or both [17,18]. For example, the location and existing resources are pull factors when assessing the attractiveness of a potential destination [16,19,20].…”
Section: Introductionmentioning
confidence: 99%